Topology Optimization of Dual Octagonal Array antenna for low frequency applications - Venu Madhav, P; M SivaGanga Prasad, Dr (International Journal of Engineering and Technology, 2018)
Objectives: Efficient antenna design for use in communication systems is altering the face of the antenna modeling. The ever-increasing demand for portable and efficient antennas is making researchers to develop innovative models [1] using advanced antenna modeling tools that comply with industrial needs and standards. Â Methods/Statistical Analysis: Antennas with lower operating frequencies have the major constraints on its size, efficiency and gain. Study on matching techniques, feeding techniques was also to be considered.Findings: Micro strip patch antennas offers considerable amount of radiation, low cost when fabricated on FR4, light weight and are conformable to suite any application. This paper projects the design, simulation and testing of a dual octagonal patch, the topology algorithm [3] is used to optimize the size and shape of the patch where octagons are spaced in the form of an array to address optimization on size and fits into wireless applications. Application/Improvements: The proposed model is tested in the standard antenna test bench comprising of microwave integrated circuit analyzer receiver MIC10kit and found to operate at a resonant frequency of 1.8 GHz with good radiation characteristics.Â Â